Language making and ownership from the perspective of writing creoles - Bartens Angela (International Association for Colonial and Postcolonial Linguistics, 2022)
In this paper, I examine the ideologies and policies on writing creoles as examples of hitherto mostly unwritten languages and test cases for language making as defined by Krämer et al. (forthcoming 2022), also considering issues of language ownership. In socalled “Western ideologies” of what constitutes a language, writing plays an important role. Orthographies and the actors behind them are of interest as, for example, certain graphemes carry heavy sociopolitical connotations, which may emphasize the question of language ownership. I will briefly discuss the orthographies of four Western Caribbean English-lexifier creoles (Belize, Nicaragua, San Andrés-Providence, and Limón) and their evolution over the past three decades in order to address these issues. A useful point of comparison is constituted by the orthographies devised for Haitian Creole and Jamaican.